Removal of Lead from Water Using Calcium Alginate Beads Doped with Hydrazine Sulphate-Activated Red Mud as Adsorbent - A. Naga Babu; G. V. Krishna Mohan; K. Kalpana; K. Ravindhranath (Journal of Analytical Methods in Chemistry, 2017)
Calcium alginate beads doped with hydrazine sulphate-treated red mud are investigated as adsorbent for extracting lead ions from water using batch methods of extraction. Different extraction conditions are optimised for maximum lead extraction. Substantial amount of lead is removed, and the adsorption ability is found to be 138.6 mg/g. Surface characterization using FTIR, EDX, and FESEM confirms that lead is “onto” the surface of the adsorbent. Thermodynamic parameters, adsorption isotherms, and kinetics of adsorption are analysed. Adsorption is “physisorption” in nature and spontaneous. The adsorbent developed can be regenerated using 0.1 M HCl. Thus regenerated adsorbent can be used as the adsorbent for further removal of lead at least 10 times, and this enables the complete removal of lead from water by repetitive use of the regenerated adsorbent. The beads facilitate the easy filtration. The methodology developed is successfully applied for removing lead from industrial waste waters.